Children with CHARGE‐Syndrome Associated Hearing Loss. (23rd August 2013) - Felton, Mark; Feltham, Penny; Henderson, Lise; Andrew, Rachel; Rothera, Michael; Bruce, Iain
Abstract : Objectives: 1) Highlight ear anomalies (external, middle, and inner ear) and types of hearing loss in children with CHARGE syndrome (CS). 2) Use cases to discuss surgical options for treating hearing loss in CS children, including bone conduction implants and cochlear implantation. Methods: Six children with CS referred to our tertiary service for management of hearing‐loss were identified. Subsequently, 4 of these children were fitted with a bone conduction implant (Baha® system), and 2 underwent cochlear implantation. For the 4 Baha® system children, free‐field speech audiometry was used to monitor hearing postoperatively. For 3 of the children, Baha® system stability was measured with resonance frequency analysis at surgery and sequentially at follow‐up visits. The two children having cochlear implants were followed up with pure tone audiometry and speech perception scores. Results: Four cases of Baha® system implantation and 2 cases of cochlear implantation in children with CS are discussed including pre‐operative assessment/selection criteria, scans, and surgical planning; operative challenges; implant stability postoperatively and hearing benefit. The mean age at surgery was 9 years 11 months (4 years 9 months to 14 years 10 months), and mean follow‐up was 18 months (6 months to 25 months). Conclusions: Children with CS and mixed hearing‐loss are challenging when considering how best to maximize hearing potential. Some children with CS will also have external ear abnormalities, potentially limiting the use of conventional BTE HAs. Bone conduction implants and cochlear implants are an effective hearing solution for selected children with CS.